ANALISIS PEMAHAMAN DAN KESADARAN DALAM MEMBAYAR ZAKAT PERKEBUNAN (STUDI KASUS PETANI KEBUN SAWIT) DI KECAMATAN BATURAJA BARAT KABUPATEN OGAN KOMERING ULU - Imelia Amanda; Rudi Aryanto; Safitri Asrol (LPPM Universitas Nias Raya, 2026)
Baturaja barat district, ogan komering ulu regency, is an area where the majority of the population works as oil palm farmers. however, farmers' understanding and awareness regarding the obligation of zakat (obligatory almsgiving) on ​​plantations remain relatively low. this study aims to analyze the level of farmers' understanding and awareness regarding the fulfillment of plantation zakat in baturaja barat district. the study employs a qualitative method with data collection techniques involving interviews, observation, and documentation, analyzed through the stages of data reduction, data presentation, and conclusion drawing. the results indicate that most farmers are familiar only with zakat fitrah and are unaware that oil palm plantation yields are subject to zakat once they reach the nisab (minimum threshold). the low level of awareness regarding zakat fulfillment is attributed to a lack of outreach and education, limited religious knowledge, and a preference for giving infaq and sadaqah (voluntary charity) directly rather than fulfilling zakat in accordance with sharia regulations. the study highlights the need for increased education and outreach regarding plantation zakat to improve farmers' understanding and awareness of fulfilling this obligation in accordance with islamic sharia.